2016
DOI: 10.1038/ncomms11147
|View full text |Cite
|
Sign up to set email alerts
|

Mercury anomalies and the timing of biotic recovery following the end-Triassic mass extinction

Abstract: The end-Triassic mass extinction overlapped with the eruption of the Central Atlantic Magmatic Province (CAMP), and release of CO2 and other volcanic volatiles has been implicated in the extinction. However, the timing of marine biotic recovery versus CAMP eruptions remains uncertain. Here we use Hg concentrations and isotopes as indicators of CAMP volcanism in continental shelf sediments, the primary archive of faunal data. In Triassic–Jurassic strata, Muller Canyon, Nevada, Hg levels rise in the extinction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 48 publications
11
168
1
Order By: Relevance
“…The Hg trends generated in this study are also compared, in Fig. 3, with the existing New York Canyon record (35), which appears to have a subtly different trend in sedimentary Hg/TOC increase, potentially resulting from atmospheric or local sedimentological processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hg trends generated in this study are also compared, in Fig. 3, with the existing New York Canyon record (35), which appears to have a subtly different trend in sedimentary Hg/TOC increase, potentially resulting from atmospheric or local sedimentological processes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study on the Triassic-Jurassic boundary section at New York Canyon (Nevada) showed an abrupt increase in Hg concentrations and Hg/TOC ratios correlated with the negative excursion in δ 13 C org that marks the end-Triassic extinction horizon (35). These Hg excursions were attributed to volcanic processes operating during the emplacement of CAMP.…”
Section: Significancementioning
confidence: 96%
“…Mercury is an excellent proxy for periods of major volcanic activity in the geological record (Grasby et al 2015;Thibodeau et al 2016). Organic matters strongly control mercury sequestration over geological time (Grasby et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sanei et al 17 demonstrated that the Siberian Trap eruption, the largest LIP in the geologic record and also associated with the largest Phanerozoic extinction event, left a characteristic mercury spike as a fingerprint in the rock record. Subsequent work has confirmed Hg spikes associated with other LIP events associated with mass extinction intervals [18][19][20][21][22][23] . Grasby et al 21 also demonstrated that background Hg levels appear constant over geologic time, showing that Hg spikes associated with LIPs are truly anomalous features of the rock record.…”
Section: Mercury As a Proxy For Lip Eventsmentioning
confidence: 84%
“…Excess mercury flux to the environment during periods of major volcanic eruption can overwhelm this natural system, creating a mercury spike relative to total organic carbon (TOC) in the rock record 17 , as a key indicator of massive volcanism. Hg stable isotope data can further verify a volcanic source of Hg spikes 20,24 . According to Blum et al 25 , Hg stable isotopes exhibit both mass-dependent fractionation (MDF, reported as δ 202 Hg) and mass-independent fractionations (MIF, reported as Δ 199 Hg) in the environment and can be used as multi-dimensional tracers to discriminate Hg sources, transport and cycling [25][26][27][28] .…”
Section: Mercury As a Proxy For Lip Eventsmentioning
confidence: 97%